2023
DOI: 10.24036/00703kons2023
|View full text |Cite
|
Sign up to set email alerts
|

High School Student’s Career Indecision Reviewed Based on Major and Gender

Abstract: Career indecision is a condition that occurs in individuals when experiencing problems or difficulties when starting or being in the career decision-making process that causes incompetence or uncertainty in determining their career choices. Career indecision is caused by various factors, both internal and external factors of the individual. In this study, the factors studied were major and gender. The analytical method used in the study was a two-way ANOVA. The study sample was 148 high school X students.  The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…Significant differences did not occur in career decision making in terms of the group/stream chosen by the students. This finding is in line with the findings of Dwatra and Adri (2023) [13] . In addition, a Mann Whitney U test showed that students who reported satisfaction with current academic performance differed significantly in career decision making from students who did not feel satisfied with their current academic performance.…”
Section: Discussionsupporting
confidence: 93%
“…Significant differences did not occur in career decision making in terms of the group/stream chosen by the students. This finding is in line with the findings of Dwatra and Adri (2023) [13] . In addition, a Mann Whitney U test showed that students who reported satisfaction with current academic performance differed significantly in career decision making from students who did not feel satisfied with their current academic performance.…”
Section: Discussionsupporting
confidence: 93%